POST-HEALTH EVALUATION BUILDING LINES AND ADMINISTRATION DEPARTMENT OF EDUCATION TECHNIQUE BUILDING FACULTY OF ENGINEERING UNY - Bambang Sugestiyadi (Jurnal Penelitian Saintek, 2002)
The study of the post occupancy evaluation of the lecturing and administrationbuildings of the Department of the Construction Engineering  Teacher Training of the Faculty  of  Technique of  Yogyakarta State  University is limited at the indicative level of the lecturing and administration buildings. It aims at investigating the technical and functional  aspects  of the lecturing and administration  rooms  of  the  Department  of  the  Construction  Engineering Teacher Training of the Faculty of Technique ofYogyakarta  State University. It is conducted in 5 months of the lecturing period  199912000, with the analysis unit of the Department of the Construction Engineering  with all of its activity aspects.  The  observing focuses   of  the  study  are  a)  the  technical  aspect, including: 1) lighting, 2) ventilation, 3) security, 4)fire fighting,  5) maintenance; b) the functional  aspect, including: 1) room organization, 2) room capacity, 3) circulation, 4) communication, 5) the possibility to change. The data is collected using interview, field  observation and documentation.  The content validity  is tested  on relational judgmental  basis.  The results  of the study show  that  in almost  50%  of  the  lecturing period  of  the  odd  semester  of  1999/2000 the lecturing room capacity is "less ", It is also found  that the ideal and comfortable lecturing rooms are those with the capacity of 30-35 individuals per classroom. Based on the results of the study, it is necessary to consider the addition of the lecturing rooms with the "big"  capacity of 100 individuals.  And, based on the results of the evaluation of the capacity of the administration and lecturer rooms show  that  90% of the capacity of the rooms  do not  meet the working room standard. The condition of the comfort and the security of the rooms do not meet the requirements. Based on the results of the study it is necessary to develop the administration and the lecturer rooms into a "vertical"  direction that they meet the comfortable working room standard.